Pulmonary Aerosol Delivery of Let‐7b microRNA Confers a Striking Inhibitory Effect on Lung Carcinogenesis through Targeting the Tumor Immune Microenvironment. Issue 17 (8th July 2021) - Zhang, Qi; Pan, Jing; Xiong, Donghai; Wang, Yian; Miller, Mark Steven; Sei, Shizuko; Shoemaker, Robert H.; Izzotti, Alberto; You, Ming
Abstract: MicroRNAs are potential candidates for lung cancer prevention and therapy. A major limitation is the lack of an efficient delivery system to directly deliver miRNA to cancer cells while limiting systemic exposure. The delivery of miRNA via inhalation is a potential strategy for lung cancer prevention in high‐risk individuals. In this study, the authors investigate the efficacy of aerosolized let‐7b miRNA treatment in lung cancer prevention. Let‐7b shows significant inhibition of B[a]P‐induced lung adenoma with no detectable side effects. Single‐cell RNA sequencing of tumor‐infiltrating T cells from primary tumors reveals that Let‐7b post‐transcriptionally suppresses PD‐L1 and PD‐1 expression in the tumor microenvironment, suggesting that let‐7b miRNAs may promote antitumor immunity in vivo. Let‐7b treatment decreases the expression of PD‐1 in CD8+ T cells and reduces PD‐L1 expression in lung tumor cells. The results suggest that this aerosolized let‐7b mimic is a promising approach for lung cancer prevention, and that the in vivo tumor inhibitory effects of let‐7b are mediated, at least in part, by immune‐promoting effects via downregulating PD‐L1 in tumors and/or PD‐1 on CD8+ T cells. These changes potentiate antitumor CD8+ T cell immune responses, and ultimately lead to tumor inhibition. Abstract : The geometric median diameter of let‐7b miRNA is 29.0 nm. Ex vivo images show that the miRNA nanoparticles specifically accumulate in the lungs, with little or no accumulation in other tissues. Let‐7b leads to increased frequency of tumor infiltrating CD8+ T cells, and shifts subsets of CD8+ tumor‐infiltrating lymphocytes (TILs) toward antitumor immunity. Combining aerosolized let‐7b with Kras Vaccine (KVax) can achieve significantly enhanced tumor‐suppressive efficacy.